Komunikasi Motivasi dan Imperatif dalam Surah Ad-Duha dan Al-Insyirah - Nur Aida (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2023)
Surah Ad-Duha and Al-Insyirah contain motivational messages and command messages from Allah to the Prophet Muhammad. This motivational and imperative communication was effective to make the Prophet excited again to continue the da'wah. This can be a lesson to motivate and order human resources, especially to carry out da'wah tasks. With qualitative research methods, this paper will analyze how the forms of motivational and imperative communication in the two suras are. The data used are surah Ad-Duha verses 1-11 and surah Al-Insyirah verses 1-8, the context of the revelation of the verse and the situation of preaching the City of Mecca at that time. As a result, the content of the motivational message is information so that you can see today's situation correctly, invites you to be grateful for the blessings you have received and information that there is hope in the future. While the contents of the command message are related to the command to preach and do good to people who are in need. The systematic communication of motivation is first followed by command communication. Sentences to invite gratitude are interrogative sentences, while to understand the situation today and tomorrow are news sentences. Then to convey the task is with a command sentence. The diction used in both the motivational and commanding messages is diction that contains positive emotional nuances, there is also a diction for emphasis. In addition, stylistics of sentence structure and rhyming sounds are also used.